Exploring the effects of outsourcing incentives on military logistics outsourcing intention - (:unkn) unknown (My University, 2008)
70'li yıllardan itibaren hızlanan ulaştırma vasıtaları, telekomünikasyon ve bilgi sistemleri şebekelerinin dünya yüzeyinin neredeyse tamamını kapsamasının sonucu küreselleşme kavramı ortaya atılmıştır. Bu olgunun ekonomik ve askeri tüm işlemleri etkisi altına almasıyla artan ve sertleşen rekabet ortamı, örgütleri maliyetleri konusunda daha dikkatli olmaya itmiştir. Soğuk Savaşın bitmesi ile beraber ABD ve tüm batı ordularında yapısal bazı değişiklikler görülmüştür. Önceden her türlü fonksiyonunu kendi bünyesinde bulunan organları ile yerine getiren ve kendi organik kuruluşu ile kendine her yerde yetmeye yönelik tasarlanmış olan ordular, küçülme ve kendi bünyesinde topladığı fonksiyonların bir kısmını dış kaynak kullanarak sağlamanın yollarını arar olmuştur.

The term "globalization" emerged as result of speeding up transportation vehicles, telecommunication and information systems networks which have been covering almost whole surface of the globe since 70's. Increasing and hardening competition influencing economic and military transactions has urged organizations to be careful about their costs. After the Cold War some structural changes have occurred primarily in USA and then all western armies. The armies, designed as self sufficient and being able to perform any function in any scene with their own components in the Cold War era, have been seeking ways to downsize and outsource some of the functions being done by military units before. The purpose of our study is to investigate the effects of the possible incentives of military logistics on the outsourcing intention. For this reason, possible incentives and the intention of logistics outsourcing based on the literature and experiences are measured and interpreted by conducting a questionnaire to army professionals employed in the level of brigade.
Dış kaynak kullanımının faydalarının askeri lojistikte dış kaynak kullanımı eğilimine etkileri üzerine bir araştırma
Keywords: Savunma Bilimleri